Type II necrotizing fasciitis - Martinez,Isabel Bramão (2022)
Abstract Necrotizing fasciitis integrates a series of necrotizing soft tissue infections. Type II necrotizing fasciitis (NF) is due to an infection by group A Streptococcus, which can be associated with Staphylococcus aureus, and may evolve to toxic shock syndrome, with high morbidity and mortality negatively influenced by delay in diagnosis and institution of appropriate surgical therapy. At an early stage, the clinical presentation may not be explicit; therefore, a high index of suspicion is essential in order to diagnose, initiate antibiotic therapy and, most importantly, perform surgical debridement in a timely manner, which is crucial for optimizing the patient's prognosis. The purpose of this article is to execute a narrative review about type II NF, namely in terms of its clinical manifestations, diagnostic and therapeutic approach, through the analysis of recent information on the subject.